Palynology and the Ecology of the New Zealand Conifers - McGlone, Matt S.; Richardson, Sarah J.; Burge, Olivia R.; Perry, George L. W.; Wilmshurst, Janet M. (Frontiers in Earth Science, 2017)
The New Zealand conifers (20 species of trees and shrubs in the Araucariaceae, Podocarpaceae and Cupressaceae) are often regarded as ancient Gondwanan elements, but mostly originated much later. Often thought of as tall trees of humid, warm forests, they are present throughout in alpine shrublands, tree lines, bogs, swamps, and in dry, frost-prone regions. The tall conifers rarely form purely coniferous forest and mostly occur as an emergent stratum above evergreen angiosperm trees. During Maori settlement in the 13th century, these fire-sensitive trees succumbed rapidly, most of the drier forests being lost. As these were also the more conifer-rich forests, ecological research has been skewed towards conifer dynamics of forests wetter and cooler than the pre-human norm. Conifers are well represented in the pollen record and we here we review their late Quaternary history in the light of what is known about their current ecology with the intention of countering this bias. During glacial episodes, all trees were scarce south of c. 40°S, and extensive conifer-dominant forest was confined to the northern third of the North Island. Drought- and cold-resistant Halocarpus bidwillii and Phyllocladus alpinus formed widespread scrub in the south. During the deglacial, beginning 18,000 years ago, tall conifers underwent explosive spread to dominate the forest biomass throughout. Conifer dominance lessened in favour of angiosperms in the wetter western lowland forests over the Holocene but the dryland eastern forests persisted largely unchanged until settlement. Mid to late Holocene climate change favoured the more rapidly growing Nothofagaceae which replaced the previous conifer-angiosperm low forest or shrubland in tree line ecotones and montane areas. The key to this dynamic conifer history appears to be their bimodal ability to withstand stress, and dominate on poor soils and in cool, dry regions but, in wetter, warmer locations, to slowly grow thorough competing broadleaves to occupy an exposed, emergent stratum where their inherent stress resistance ensures little effective angiosperm competition.